BUSINESS INTELLIGENCE IMPLEMENTATION IN MARKETING STRATEGY IN START UP PERFORMANCE - Achmad Fauzi; Jhonni Sinaga; Immanuel Pharosandika Sihombin; Indah Wulandari; Amelia Seli Febrianti; Selliatun Nuriah; Eny Trisno Wanti; Naufal Khairiansyah (Draf Solusi Indonesia, 2023)
Intelligence implementation in marketing strategy Competition in the field of marketing is increasing, the implementation of artificial intelligence has become an increasingly important topic in the digital era. Now it can help startup companies process data more quickly and efficiently, enabling them to make smarter decisions and make the most of their own marketing strategy. Rules or systems that can be used in marketing is through customer data analysis. By using rules or machine learning processes, companies can analyze the existing behavior and uses of their customers, and predict their future needs and wants. Thus, companies can customize their products or services and enhance their marketing to achieve the business goals that startup companies require.